Epidermoid cyst in lower lip mimicking mucocele: A rare entity with review of literature - Ketaki Kinikar; Venkateswarlu Meduri; Avinash Tejasvi; Harsha Bhayya (Wolters Kluwer Medknow Publications, 2016)
An epidermoid cyst is the most common cutaneous cyst, which is rarely observed in the oral cavity. Epidermoid cysts are the result of the proliferation of the surface epidermal cells within the dermis, which may occur anywhere in the body; however, approximately 6.9% are found in the head and neck region, with less than 0.01% incidence of all oral cavity cysts. In this report, we present a rare case of a labial epidermoid cyst in a 27-year-old woman with complaints of swelling and facial asymmetry in the lower lip beneath the left commissure for 3 years.